Overview of Thirty Semantic Formalisms for Reo - S.-S. T.Q. Jongmans; F. Arbab (Scientific Annals of Computer Science, 2012)
Over the past decades, coordination languages have emerged for the specification and implementation of interaction protocols for communicating software components. This class of languages includes Reo, a platform for compositional construction of connectors. In recent years, many formalisms for describing the behavior of Reo connectors have emerged. In this paper, we give an overview of all these classes of semantic models. Furthermore, we investigate the expressiveness of two more prominent classes, constraint automata and coloring models, in detail.